A swarm intelligent approach to data ferrying in sparse disconnected networks. Issue 6 (2nd November 2021) - Fraser, Bradley; Hunjet, Robert; Coyle, Andrew
Abstract: Swarming and emergent behaviour techniques can offer simple control schemes for the organisation of many nodes, with little communications overhead and processing time. These mechanisms are robust against node losses, and are able to run on cheap, disposable platforms. This article examines the usefulness of a swarming technique to address data ferrying in disconnected networks to provide delay-tolerant type communications. Mathematical analysis of a pheromone-based ferrying approach reveals a robust solution to the round-robin ferrying problem. Simulation results from static and dynamic network topologies agree with the mathematical model and show encouraging results in coordinating data ferries in a disconnected environment. Graphical Abstract: UF0001 A simulated scenario of UAVs intelligently ferrying data between deployed tactical nodes in a RF contested environment.